A RAD51 assay feasible in routine tumor samples calls PARP inhibitor response beyond BRCA mutation. Issue 12 (30th October 2018) - Castroviejo‐Bermejo, Marta; Cruz, Cristina; Llop‐Guevara, Alba; Gutiérrez‐Enríquez, Sara; Ducy, Mandy; Ibrahim, Yasir Hussein; Gris‐Oliver, Albert; Pellegrino, Benedetta; Bruna, Alejandra; Guzmán, Marta; Rodríguez, Olga; Grueso, Judit; et al.
Abstract: Poly(ADP‐ribose) polymerase (PARP) inhibitors (PARPi) are effective in cancers with defective homologous recombination DNA repair (HRR), including BRCA1/2‐related cancers. A test to identify additional HRR‐deficient tumors will help to extend their use in new indications. We evaluated the activity of the PARPi olaparib in patient‐derived tumor xenografts (PDXs) from breast cancer (BC) patients and investigated mechanisms of sensitivity through exome sequencing, BRCA1 promoter methylation analysis, and immunostaining of HRR proteins, including RAD51 nuclear foci. In an independent BC PDX panel, the predictive capacity of the RAD51 score and the homologous recombination deficiency (HRD) score were compared. To examine the clinical feasibility of the RAD51 assay, we scored archival breast tumor samples, including PALB2‐related hereditary cancers. The RAD51 score was highly discriminative of PARPi sensitivity versus PARPi resistance in BC PDXs and outperformed the genomic test. In clinical samples, all PALB2‐related tumors were classified as HRR‐deficient by the RAD51 score. The functional biomarker RAD51 enables the identification of PARPi‐sensitive BC and broadens the population who may benefit from this therapy beyond BRCA1/2‐related cancers. Synopsis: Sensitive and highly specific biomarkers usable in archived formalin fixed parafin embedded (FFPE) tumour samples are needed to extend the use of PARP inhibitors beyond BRCA1/2‐related cancers. The RAD51 score may satisfy this clinical unmet need. The RAD51 score shows complete discriminative capacity in predicting PARP inhibitor response. The RAD51 score is feasible in routine breast tumor samples without prior exposure to DNA damaging agents. Carrying a PALB2 mutation is associated with a low RAD51score. Abstract : Sensitive and highly specific biomarkers usable in archived formalin fixed parafin embedded (FFPE) tumour samples are needed to extend the use of PARP inhibitors beyond BRCA1/2‐related cancers. The RAD51 score may satisfy this clinical unmet need.